ANALYSIS OF LEADERSHIP STYLE ON PERFORMANCE (CASE STUDY EMPLOYEE OF DIRECTORATE OF INFRASTRUCTURE INVESTMENT DEVELOPMENT, MINISTRY OF PUBLIC WORKS AND HOUSING) - Jeffy Alfanny (Institut Teknologi Sepuluh Nopember, 2018)
Leadership is a key element in an organization. The soul of leadership must beowned by every leader who has the main task of managing activities in theorganization. This study aims to determine the desired leadership style in theworking environment of Directorate of Infrastructure Investment Development(DBII), Ministry of Public Works and Housing. This research uses aquantitative approach using survey method, priority-scale approach,regression analysis and focus group discussion (FGD). The results showed thatthere were at least 3 (three) leadership styles commonly used by leaders namely,authoritarian, delegative and participatory styles. Based on the survey andFGD results, participative leadership style is the preferred style of leadershipin the work environment of the Directorate of Infrastructure InvestmentDevelopment while the regression results show that the leadership style ofparticipatory has a positive influence with performance. Participativeleadership style can be implemented in leadership development activities in theworking environment of Directorate of Infrastructure Investment Developmentbut still needed coordination and agreement from the internal party and relatedexternal institution having capacity and competence in human resourcedevelopment.